Banjar Culture in The Anthology of Poetry Hulu Sungai Tengah In Pantun and Poetry - Johan Arifin; Heppy Lismayanti; Jamilah Jamilah (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research is related to Banjar culture in the poetry anthology Hulu Sungai Tengah in Pantun and Poetry published by Scripta Cendikia. The purpose of this study is to reveal and describe the elements of Banjar culture contained in the poetry anthology Hulu Sungai Tengah in Pantun and Poetry published by Scripta Cendikia, which includes (1) Linguistic Aspects, (2) Community System, (3) Livelihood System. The approach used is an anthropological approach, carried out with descriptive methods of analysis and digging up data taken using textobservation techniques and documentation techniques. After the data is collected then analyzed with interpreatative descriptive techniques, where researchers explain the data as a whole first, after the data is collected and netted researchers interpret to analyze the data carried out through stages: (1) Organizing data, (2) interpretation, (3) evaluation. Based on the results of the study, the following conclusions were obtained: (1). Linguistic aspects which include: a) phonological dominant with vowel sounds a, e, i, and u b) lexical there are 321 words that predominantly contain vowel sounds a, e, i, and you, there are also many word repetitions, c) grammatical, arranged linearly and there are no structural deviations. (2). Social System, (a) relations between communities, found in this study are 7 poems that describe that between communities are interconnected. (b) Society with social environment found in this study there are 13 poems that describe that society and its social environment are interdependent. (3). The livelihood system found in this study is agriculture such as rice fields, grains (rice) and rice, as well as trade, namely markets.